As estratégias de criação e localização dos outlets: um estudo de caso sobre o Complexo Integrado Catarina localizado no município de São Roque-SP - Santos, Joe Andrew Mateus (Universidade Federal de São Carlos, 2019)
Trade and consumption have a significant relevance in geography studies, after all, influences social life in multiple aspects and also in the formation and transformation of geographical space, especially the urban one. Taking into account their multiformity, this research analyzed one of several commercial forms outlets, having as object of research Catarina Fashion Outlet, built in the municipality of São Roque, located in the Sorocaba Metropolitan Region in the state of São Paulo. This research object was chosen because it is the only one located in this metropolitan region and is part of a complex made up of business towers and the first executive airport in the country, and this outlet has a great representation as a consumer space for the population. this and other regions of the state. Our research aimed to analyze the commercial dynamics of this typology, especially the elements that make possible the desired discounts on luxury goods, such as features such as location and architecture, as well as their role in urban (re) spatial production and in contemporary times. The research methodology included a bibliographic and documentary survey, in addition to the procedures performed in the field: fieldwork, photographic records through non-participant observation.The research found the uniqueness of this commercial form due to the set of elements that characterize it, but mainly by its commercial strategies and its location that takes into consideration the regional context, placing itself as another modern commercial form attracting new content, forms and according to new logic and changes in the market and consumption.
Outlet creation and location strategies: a case study on the Catarina Integrated Complex, São Roque city.
Keywords: Comércio; Consumo; Outlet; Mercadoria; Localização; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA